PENENTUAN WILAYAH-WILAYAH UNGGULAN PENGEMBANGAN TERNAK BESAR DI PROVINSI NUSA TENGGARA TIMUR - Firman, Achmad; Nono, Obed Haba (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2019)
This study aims to determine the central areas for the development of large livestock in the East Nusa Tenggara Province. The data used in this study are secondary data obtained from the Central Statistics Agency and the Agriculture Service of East Nusa Tenggara Province. The analytical method used in this study is a quantitative method. The results of this study indicate that the areas that can be used as centers for large livestock development are as follows: (1) the development of cattle livestock is found in Kupang, Timor Tengah Selatan, Belu, Alor, Ende, Rote, Malaka, and Kupang city (2) Development of horse is found in Sumba Barat, Lembata, Flores Timur, Sikka, Ngada, Sumba Tengah, Sumba Barat Daya, Manggarai Timur, Sabu Raijua; and (3) Development of buffalo is found in Sumba Barat, Sumba Timur, Ngada, Rote, Manggarai, Sumba Tengah, Sumba Barat Daya, nagekeo, Mangarai Timur, Sabua Raijua.